A Study on the Effectiveness of Picture Series Method in Improving the Writing Ability of Recount Text for Junior High School Students - Heppy Theresia Sitompul (Centre for Literary and Cultural Studies, 2023)
This article discusses the importance of developing recount text writing skills for junior high school students in English language learning. In the 2013 curriculum, English language skills are very important in preparing a generation that can compete globally. However, writing skills often receive less attention, and students tend to write only because the teacher commands them. The picture series method is an effective approach to improving the ability to write recount texts. This method involves a series of pictures to help students string past events into a structured narrative. The results showed that the picture series method can increase students' learning motivation, overcome barriers in writing, and strengthen teacher-student relationships. This research uses a literature review approach and field research at SMP Negri 4 Pematang Siantar to collect data on the effectiveness of the serial image method in improving the ability to write recount texts. Through literature analysis and observation of students, it was found that most students showed interest and enthusiasm in using the serial image method. A total of 81% of students succeeded in writing recount texts with the help of this method. In conclusion, the picture series method is effective in overcoming the problem of students' writing ability and improving learning interaction. This article suggests that teachers use the series picture method to learn to recount texts to create a more interesting and creative learning environment for junior high school students. This method can help students develop better thinking skills, emotional responses, and writing skills.